Eksplorasi Jejaring Farmakologi pada Tanaman Yakon Untuk Pengobatan Diabetes Mellitus Tipe 2 (DMT2) - Azzahra, Fatimah; Dwi Astuti, Ayun; Masyita, Ayu (Jurnal Jaring SainTek, 2024)
Diabetes Mellitus remains a pressing concern due to a significant surge in cases, driving the continuous exploration of natural substances as potential drugs and nutraceuticals. Notably, insulin leaves or yacon are among the promising natural candidates. Previous in vitro and in vivo studies have established the antidiabetic effects of insulin leaves, and in silico investigations have also been conducted to assess their impact on DPP-4. Nonetheless, the exploration of the hypoglycemic or antidiabetic effects of this plant remains extensive and offers room for further investigation. In light of this research, PPI analysis and oncology gene enrichment were carried out on target compounds and diseases using bioinformatics databases, Venn diagrams, Cytoscape, and ShinyGO. The findings unveiled 9 high-priority targets from the analysis, and the KEGG pathway that elucidates the disease mechanism is the EGFR inhibitor resistance pathway.